2019
DOI: 10.1016/j.jbmt.2019.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Myofascial pain and treatment: Editorial a critical overview of the current myofascial pain literature – August 2019

Abstract: This quarter's overview of the myofascial pain literature includes quite a few basic research papers in addition to the usual high quantity of dry needling (DN) papers. Of particular interest are a study by Fischer and colleagues studying the role of mitochondrial functions in chronic trigger points (TrPs) (Fischer et al 2018), a study by Li and associates who conducted a quantitative proteomics analysis to identify biomarkers of chronic myofascial pain and therapeutic targets of dry needling in a rat model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…These studies demonstrated good results in terms of pain reduction compared to both sham intervention and ultrasound, although it was similar to the effect of ischemic compression. It can be speculated that the key to the success in the present study was to apply PRT in two anatomical regions, the cervical and trigeminal region, since both masticatory and cervical muscles can refer pain to the orofacial and temporomandibular areas [11].…”
Section: Primary Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…These studies demonstrated good results in terms of pain reduction compared to both sham intervention and ultrasound, although it was similar to the effect of ischemic compression. It can be speculated that the key to the success in the present study was to apply PRT in two anatomical regions, the cervical and trigeminal region, since both masticatory and cervical muscles can refer pain to the orofacial and temporomandibular areas [11].…”
Section: Primary Outcomementioning
confidence: 99%
“…Nevertheless, the main reason for clinical consultation is chronic and persistent orofacial pain [10]. A common clinical nding is that TMD pain can originate in so-called trigger points (TrPs) of the masticatory and cervical muscles, which refer pain to the orofacial and temporomandibular regions [1,11]. TrPs are however enigmatic as the underlying pathophysiology remains unclear and the speci c differences between TrPs and points in the muscles that are simply tender or painful to palpation continue to be discussed [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…10 A common clinical finding is that TMD pain can originate in so-called trigger points (TrPs) of the masticatory and cervical muscles, which refer pain to the oro-facial and temporomandibular regions. 1,11 TrPs are however enigmatic as the underlying pathophysiology remains unclear and discussed. 12,13 The therapeutic approach to myofascial TMD should focus on pain relief and rehabilitation of function and to prevent or remove predisposing and/or perpetuating factors, by non-invasive, simple and reversible therapies that adhere to the biopsychosocial approach such as conservative dentistry, physiotherapy and psychology.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…It can be speculated that the key to the success in the present study was to apply PRT in two anatomical regions, the cervical and trigeminal region, since both masticatory and cervical muscles can refer pain to the oro-facial and temporomandibular areas. 11 Secondary outcomes. In relation to secondary outcome measures it was observed that for all PPTs the effects only depended on time.…”
Section: Samplesmentioning
confidence: 99%
“…Another theory suggests that prolonged muscle contraction is an offending mechanism, resulting in local tissue ischemia and the accumulation of metabolic byproducts. These events perpetuate a cycle of motor and sympathetic activity that leads to a pain response, which can persist even after removal of the initial stimulus 19 . Given these proposed pathophysiology's of MPS, it is believed that mechanical disruption with a needle, with or without injectate, is necessary to terminate the nerve endplate dysfunction and allow for prolonged pain relief 6 .…”
Section: Pathophysiology Of Trigger Pointsmentioning
confidence: 99%